The reversal of roles as the reasoning for remaining Christian in the face of hardship in the First Epistle of Peter - Van der Watt, J.G. (Jan Gabriel), 1952- (University of Pretoria, 2013)
Thesis (PhD (New Testament Studies))--University of Pretoria, 2007.